2011 IEEE 11th Topical Meeting on Silicon Monolithic Integrated Circuits in RF Systems 2011
DOI: 10.1109/sirf.2011.5719331
|View full text |Cite
|
Sign up to set email alerts
|

RF extraction of self-heating effects in FinFETs of various geometries

Abstract: Dynamic self-heating effect is characterised in n-channel FinFETs on Silicon-on-Insulator (SOI) platform. RF extraction technique is discussed and dependence of thermal resistance on fin width, number of parallel fins and fin spacing is studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…N‐channel MOSFETs with gate lengths L g ranging from 30 to 100 nm, finger width W f = 250 nm, and number of parallel fingers N f = 80 were characterized. Threshold voltages, V th , extracted in the linear regime at a drain voltage V d = 20 mV were shown to be ~0.38–0.4 V .…”
Section: Self‐heating Effectsmentioning
confidence: 97%
See 4 more Smart Citations
“…N‐channel MOSFETs with gate lengths L g ranging from 30 to 100 nm, finger width W f = 250 nm, and number of parallel fingers N f = 80 were characterized. Threshold voltages, V th , extracted in the linear regime at a drain voltage V d = 20 mV were shown to be ~0.38–0.4 V .…”
Section: Self‐heating Effectsmentioning
confidence: 97%
“…In the case of FinFETs, the reduction of fin width, and consequently effective width, results in a higher surface‐to‐volume ratio and different effects on thermal resistance (associated with device surface) and thermal capacitance (associated with Si volume). In , it has been demonstrated that there is a decrease of the thermal time constant with a reduction of the fin width. The thermal time constant is around 80 ns for the narrowest fins (12 nm).…”
Section: Self‐heating Effectsmentioning
confidence: 99%
See 3 more Smart Citations